Chlamydial infections in swine industry and their significance - KRITAS (Σ.Κ. ΚΡΗΤΑΣ) S. K.; SAOULIDIS (Κ. ΣΑΟΥΛΙΔΗΣ) K.; TSINAS (Α. ΤΣΙΝΑΣ) A.; PAPADOPOULOS (Ο. ΠΑΠΑΔΟΠΟΥΛΟΣ) O.; KYRIAKIS (Σ.K. ΚΥΡΙΑΚΗΣ) S. K. (Journal of the Hellenic Veterinary Medical Society, 2018)
Chlamydial infections in animals, particularly those in ruminants and poultry, have been well studied for the last decades. However, no much information exist on such infections in pigs. This paper reviews the recent knowledge in various countries as well as in Greece on the role of the microorganism on causing disease in swine with emphasis on pathogenesis, epizootiology and diagnosis. Particular attention is given on the newly-described chlamydial strains as well as the recent experimental information and views which implicate the microbe as pathogen. Finally, some measures with respect the prevention and control against Chlamydiae are suggested for the Greek pig industry.